Challenges Faced by First-Year Students Based on Individual Identities: The Case of the College of Basic Education, University of Duhok - Ahmed Hassan, Shaima (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2024)
This study examines the challenges faced by first-year students at the College of Basic Education, University of Duhok. The research focuses on the impact of individual identities on academic and social integration. A quantitative descriptive methodology was used, employing structured questionnaires. The study reveals a range of obstacles that extend beyond initial expectations and are consistent across gender and departmental lines. The analysis shows that there is a crucial requirement for a support framework that is universally accessible and inclusive, designed to aid students in their transition to higher education. The findings of the study recommend the creation of comprehensive feedback mechanisms and interdepartmental cooperation in the development of support programs. The research emphasizes the significance of acknowledging and addressing the distinct obstacles encountered by students with intersecting marginalized identities. Suggestions for future research involve a more thorough examination of the long-term impacts of these obstacles and the investigation of focused interventions to improve student achievement and well-being. This study adds to the discussion on improving student support services and creating an inclusive academic environment that promotes the growth and development of all students, especially those who are navigating their first year in higher education.